Calculation of retirement pensions in the Private Pension System: uncovering the black box - Bertolotto, Juan (2016)
The calculation of retirement pensions in the Private Pension System, when tackled by the public media, leaves the wrong impression of being an incomprehensible subject. Certainly it has an important technical component, based in financial estimates and statistics, but starting with common sense elements adequately explained, a sound understanding of the foundations regarding the calculation of retirement pensions could be attained.The aim of this article is, then, to present such foundations and gradually introduce the various technical components in a way that the reader can grasp the fact that calculation of retirements pensions is not the complicated matter it appears to be. For that purpose, we will start with some basic concepts, such as the life and death probabilities that emanate from mortality charts, and the average life expectancy and risk of longevity, so that finally, through examples, pensions from a saved capital can be calculated.